Synthesis Of Bio-Inorganic Nanohybrids Material (Binhs) Of Deoxyribonucleic Acid Encapsulated Into Layered Double Hydroxide - Suyub, Iswan Budy (2008)
Deoxyribonucleic acid (DNA) from salmon sperm was encapsulated into the inorganic Zn/Al-layered double hydroxides (LDHs) interlamellar for the formation of bio-inorganic nanohybrids materials (BINHs) by self-assembly method. Intercalation of DNA into Zn/Al-layered double hydroxides inorganic interlamellar host was carried out at different Zn to Al molar ratios, Rs and various concentrations of DNA. This work is meant to synthesize BINHs as drug or gene carrier. Among the numerous DNA delivery approaches developed so far, viral methods are well known and can be extremely efficient as its were used in the first human gene therapy test, but the safety especially the toxicity and immunogenecity of viral vectors is unknown. The physicochemical properties of the as-synthesized LDH and the resulting BINHs nanocomposite were studied using powder x-ray diffraction (PXRD) analysis. Expansion of basal spacing to about 21.2 Å (for R=3 with highest concentration of DNA which is 100 mg/ml) and 21.9 Å (for R=1 with lowest concentration of DNA which is 44.4 mg/ml) in the resulting nanomaterials was observed compared to their respective LDHs precursor with basal spacing of 9.0 Å and 8.9 Å, respectively. This shows that the expansion is due to spatial orientation of the DNA into the LDH inorganic interlamellar and FTIR spectra further confirmed that the DNA was intercalated into the host-matrix of the LDHs. Polymerase Chain Reaction (PCR) analysis verified that DNA within LDH interlayer still sustained its integrity because amplification of certain region of DNA can still be carried out.